APLIKASI PENGENALAN KOMPETENSI DASAR TEKNIK KOMPUTER DAN JARINGAN BERBASIS ANDROID SEBAGAI MEDIA BELAJAR SISWA ( STUDI KASUS SMKN 1 PANGAKALAN KERINCI ) - Muhardi, Muhardi (Riau Journal Of Computer Science, 2019)
Technological developments at this time are very rapid and have been touched to all ages and all fields. Learning media as a tool and a means to study a field of science education continues to grow every year. With the application of learning media and basic competence TKJ-based android is expected to be a companion learning media that make students more easily understand and understand learning about basic competence TKJ through android-based smartphone